La reprise des pluies et la recrudescence des inondations en Afrique de l'Ouest sahélienne - Nouaceur, Zeineddine (Physio-Géo, 2020)
This study focuses on the West African Sahel, which makes the transition between a fairly watered Sahelo-Sudanian zone and the Saharan desert. This territory covers 12 countries forming a longitudinal band between 12 and 20° North latitude. In West Africa, six countries (Senegal, Mauritania, Mali, Niger, Burkina Faso and Chad) belong to this region.In order to determine the rainfall trend in three countries of this wide territorial strip (Mauritania, Senegal, Burkina Faso), we use the graphical chronological method of information processing (MGCTI) of the "Matrix BERTIN" type. Analysis of precipitation data shows a resumption of precipitation since the late 1980s or 1990s. It follows the long Sahelian drought that began in 1970.Analysis of extreme precipitation in the study area also shows a close relationship with the surface temperature of the North Atlantic Ocean (TNA) and a strong link with the cumulative energy of tropical cyclones (ACE). This resumption of the rains, which is somewhat reminiscent of the years of "fat cows" (1950-1960 wet cycle) is however marked by an unprecedented resurgence of urban floods. These events are due, on the one hand, to the intensification of rainfall and, in the other hand, to poorly controlled urban development. Cette étude porte sur le Sahel ouest-africain, qui fait la transition entre la zone sahélo-soudanienne assez arrosée et le désert saharien. Ce territoire s'étend sur 12 pays formant une bande longitudinale comprise entre 12 et 20° de latitude Nord. En Afrique de l'Ouest, six pays (Sénégal, Mauritanie, Mali, Niger, Burkina Faso et Tchad) appartiennent à cette région.Afin de déterminer la tendance pluviométrique dans trois pays de cette large bande territoriale (Mauritanie, Sénégal, Burkina Faso), on utilise la méthode graphique chronologique de traitement de l'information (MGCTI) de type "Matrice BERTIN". L'analyse des données pluviométriques montre une reprise des pluies depuis la fin des années 1980 ou les années 1990. Elle fait suite à la longue sécheresse ...